2007
DOI: 10.1055/s-2007-981361
|View full text |Cite
|
Sign up to set email alerts
|

Die pränatale Detektion der Trisomien 13, 18 und 21: Vergleich des Advanced First Trimester Screenings (AFS)® mit dem Ersttrimester-Screening nach Nicolaides

Abstract: The calculation with AFS generated more precise risk estimations for trisomy 13, 18, and 21. An examination in large, prospective studies may be recommended to consider an introduction of this novel test strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
3
Order By: Relevance
“…High β-hCG concentrations in early pregnancy are believed to directly activate the TSH receptor. [15][16][17] Glinoer et al reported that β-hCG concentration in early pregnancy is negatively correlated with TSH concentration in blood serum and positively correlated with free T4 concentration. 18 Some studies have suggested that thyroid hormones affect the secretion of placental hormones, including β-hCG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High β-hCG concentrations in early pregnancy are believed to directly activate the TSH receptor. [15][16][17] Glinoer et al reported that β-hCG concentration in early pregnancy is negatively correlated with TSH concentration in blood serum and positively correlated with free T4 concentration. 18 Some studies have suggested that thyroid hormones affect the secretion of placental hormones, including β-hCG.…”
Section: Discussionmentioning
confidence: 99%
“…It allows calculating the individual genetic risk of aneuploidy. [13][14][15] However, additional factors, such as smoking, medications, body weight, in vitro fertilization, type 1 diabetes, may influence the levels of the parameters tested. As a result, a higher percentage of false results can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Alle Ergebnisse oberhalb dieser Grenze sollten zur Empfehlung f ü r eine weiterf ü hrende invasive Diagnostik f ü hren. Bereits in mehrere Studien wurde eine Senkung der Falschpositiv-Rate durch das AFS im Vergleich zum ETS gezeigt [13,14] . Dies bedeutet in der Praxis eine Reduktion von unn ö tigen invasiven Abkl ä rungen.…”
Section: Einleitung ▼unclassified
“…En cambio, PIA y PRC ofrecen algoritmos adicionales para calcular los riesgos de trisomías 13 y 18. Esto significa que la tasa de falsos positivos probablemente aumentaría en estos dos programas si se ofrece un cálculo de riesgo completo, que incluye las tres aneuploidías 22 . En ese caso AFS presentaría un rendimiento superior en comparación a PIA y PRC.…”
Section: Casos De Síndrome De Down No Detectadosunclassified